Three-dimensional bioprinting of a full-thickness functional skin model using acellular dermal matrix and gelatin methacrylamide bioink. (1st September 2021) - Jin, Ronghua; Cui, Yuecheng; Chen, Haojiao; Zhang, Zhenzhen; Weng, Tingting; Xia, Sizhan; Yu, Meirong; Zhang, Wei; Shao, Jiaming; Yang, Min; Han, Chunmao; Wang, Xingang
Abstract: Treatment of full-thickness skin defects still presents a significant challenge in clinical practice. Three-dimensional (3D) bioprinting technique offers a promising approach for fabricating skin substitutes. However, it is necessary to identify bioinks that have both sufficient mechanical properties and desirable biocompatibilities. In this study, we successfully fabricated acellular dermal matrix (ADM) and gelatin methacrylamide (GelMA) bioinks. The results demonstrated that ADM preserved the main extracellular matrix (ECM) components of the skin and GelMA had tunable mechanical properties. Both bioinks with shear-thinning properties were suitable for 3D bioprinting and GelMA bioink exhibited high printability. Additionally, the results revealed that 20% GelMA with sufficient mechanical properties was suitable to engineer epidermis, 1.5% ADM and 10% GelMA displayed relatively good cytocompatibilities. Here, we proposed a new 3D structure to simulate natural full-thickness skin, which included 20% GelMA with HaCaTs as an epidermal layer, 1.5% ADM with fibroblasts as the dermis, and 10% GelMA mesh with human umbilical vein endothelial cells (HUVECs) as the vascular network and framework. We demonstrated that this 3D bioprinting functional skin model (FSM) could not only promote cell viability and proliferation, but also support epidermis reconstruction in vitro . When transplanted in vivo, the FSM could maintain cell viability for at least 1 week. Furthermore, the FSM promoted wound healing and re-epithelization, stimulated dermal ECM secretion and angiogenesis, and improved wound healing quality. The FSM may provide viable functional skin substitutes for future clinical applications. Statement of significance: We propose a new 3D structure to simulate natural full-thickness skin, which included 20% GelMA with HaCaTs as an epidermal layer, 1.5% ADM with fibroblasts as the dermis, and 10% GelMA mesh with HUVECs as the vascular network. It could not only maintain a moist microenvironment and barrier function, but also recreate the natural skin microenvironment to promote cell viability and proliferation. This may provide viable functional skin substitutes for future clinical applications. Graphical abstract: Image, graphical abstract